Resolução de equações quadráticas: um resgate histórico dos métodos e uma proposta de aplicação da sequencia fedathi no seu ensino - Castelo, Joâo Alfredo Montenegro (2013)
We develop in this paper a study about the equations of the second degree in a historical context that aims to give the mathematics teacher of primary and secondary education conditions of instigating the students to raise important questions about it and increasing their interest and consequently improving their learning. To achieve this goal, we use Chapter 2 of this work to put the history of mathematics in a general context and it also show some of the ways that ancient people worked quadratic equations. In this Chapter, we write about the following methods: Arabic, Egyptian, Mesopotamian (Babylonian), Greek, Hindu, Chinese and European. We researched the ways of approaching the teaching of the equations of the second degree, who ran a simple presentation of the known formula "Bhaskara" and reserve the Chapter 3 to suggest an application example of the "Sequence Fedathi" which creates and enables a hierarchy of moments that can be worked through its history. In the last chapter, we present some considerations under the work of LAGES (2001), which suggests some surveillance on certain elements related to some high school textbooks , and particularly the content that was the subject of this investigation. Finally, we add some attachments which show a little about the life and work of two important mathematicians of antiquity: Bhaskara (Hindu) and Al-Khwarizmi (Arabic) as well as exposing some old problems as suggestions for use in class.